2011
DOI: 10.4028/www.scientific.net/amr.324.105
|View full text |Cite
|
Sign up to set email alerts
|

Improved Endothelialisation on Nanostructured Surfaces

Abstract: . Topography plays a major role on surface-cell interaction beside the surface chemistry. We investigated the effect of the nanotopography on vascular cell adhesion and proliferation in order to improve endothelialisation for restenosis treatment. In this context, Al2O3 nanowires (NWs) composed of a stable Al2O3 shell and an Al core were synthesized by chemical vapour deposition (CVD) of the molecular precursor (tBuOAlH2)2. After the detailed material characterization, human umbilical vein endothelial cells (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…The decrease in cell viabilities and populations can be explained by the difference in the surface topography induced by the deposited 1D Al 2 O 3 nanostructures [ 18 , 19 ]. However, overcoating of 1D Al 2 O 3 nanostructures with re-phages led to a clear increase in cell populations and viabilities around 40% and 30%, respectively, as compared to 1D Al 2 O 3 nanostructures.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in cell viabilities and populations can be explained by the difference in the surface topography induced by the deposited 1D Al 2 O 3 nanostructures [ 18 , 19 ]. However, overcoating of 1D Al 2 O 3 nanostructures with re-phages led to a clear increase in cell populations and viabilities around 40% and 30%, respectively, as compared to 1D Al 2 O 3 nanostructures.…”
Section: Resultsmentioning
confidence: 99%
“…Our results showed that there is a preference of HUVEC adhesion on nanowires in comparison to that of HUVSMC. 71 The control of the cell-surface interaction by the topography may represent a key issue for the future stent material design.…”
Section: Implants and Bioactive Surfaces With Al/al 2 O 3 Nanostructuresmentioning
confidence: 99%
“…Previously we have shown the effect of the topography (regardless from the surface chemistry) on the cell adhesion and proliferation using randomly distributed Al 2 O 3 structures prepared by pulsed laser treatment of biphasic Al/Al 2 O 3 nanowires (NWs). Especially surfaces which are composed Al 2 O 3 nano‐ and microstructures seem to improve adhesion and proliferation of normal human dermal fibroblasts (NHDF) . On the other hand in some applications such as targeted re‐innovation, a directional growth of cells is also desired in addition to improved adhesion and proliferation.…”
Section: Introductionmentioning
confidence: 99%